City Charter and Ordinances of the City of Lake Forest, Lake County, State of Illinois Page 88 (1894) § 11 - (:unkn) unknown (General Publisher, 1893)
Prohibited firing off a gun or pistol within the city limits. Violators fined not exceeding thre dollars for such offense.
--
Keywords: DISCHARGE